Institutional and Resource Dependence Determinants of Responsiveness to Work-Family Issues - Ingram, Paul; Simons, Tal (Academy of Management Journal, 1995)
Whether and how organizations choose strategies that address pressures from both their exchange and the institutional environments has recently become a central question in organization theory. We used the National Organizations Study to replicate and extend Goodstein's application of Oliver's framework integrating resource dependence and institutional theories to explain organizational responsiveness to work-family issues. We found that organizations' responsiveness to work-family issues was determined by both the institutional environment and demands for work-family programs from important exchange partners.